(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This year is the 200-th anniversary of the great Kazakh poet, a keen master of improvisatory art Suyunbay Aronuly. For this purpose, we aim to analyze short-sized aytises of Suyunbay akyn. Until now, the main attention of scholars was focused on large-volume aityses of Suyunbay together with Tezek-tore and a Kyrgyz great akyn Katagan. As for short-sized aytises, they remained outside the view of scholars. The author attempts to fill this gap. Therefore, we have carefully analyzed short, wise, great aytises of the prominent zhirau with Kantarbay, Zhantay, Maylikozha. As a result, in accordance with Kazakh people and with the work «The golden figure of Zhetisu poets» by our distinguished writer Mukhtar Auezov, Suyunbay is a true, talented poet, akyn. Besides, it should be noted that the poet’s language is imaginative, artistic, magnificent, marvelous. In the process of writing the paper, historical-functional, historical-genealogical methods were used.